Maintained Smoking Cessation for 6 Months Equilibrates the Percentage of Sputum CD8+ Lymphocyte Cells with That of Nonsmokers - Izolde Bouloukaki; Maria Tsoumakidou; Constantine I. Vardavas; Ioanna Mitrouska; Eleni Koutala; Nikolaos M. Siafakas; Sophia E. Schiza; Nikos Tzanakis (Mediators of Inflammation)
Little is known about the longitudinal effects of smoking cessation on sputum inflammatory cells. We aimed to investigate the changes in sputum inflammatory cells and T-lymphocyte subpopulations after 6 and 12 months smoking cessation. Induced sputum was obtained from 68 healthy smokers before and after 6 months (n=21) and 1 year (n=14) smoking cessation and from ten healthy never-smokers. Inflammatory cells were identified by morphology and T-lymphocyte subpopulations by flow cytometry. Sputum macrophages were decreased after 12 months of smoking cessation in comparison to baseline, while neutrophils increased. Moreover, CD8+ T-cells were decreased in smokers before smoking cessation compared to never-smokers and increased in smokers after 6 months of smoking cessation in comparison to baseline; result that was maintained after 1 year of smoking cessation. These novel findings indicate that smoking cessation can equilibrate certain inflammatory cells of smokers with those of nonsmokers, within 6 months of smoking cessation.